Sexual Excitation in Young Women with Different Levels of Sexual Satisfaction in Relationships: A Laboratory Study - María del Mar Sánchez-Fuentes; Ana Álvarez-Muelas; Oscar Cervilla; Reina Granados; Juan Carlos Sierra (Behavioral Sciences)
Sexual satisfaction is an important dimension of sexual health. Despite there being evidence about its relations with sexual arousal, this association has not been addressed considering arousal as a trait and as a state. Therefore, the goal of this laboratory study was to examine, in young women with different levels of sexual satisfaction in their relationships, sexual arousal as a trait (i.e., propensity for sexual excitation/inhibition) and as a state (i.e., genital response and self-reported sexual arousal to a video with explicit sexual content). The sample was composed of 45 Spanish heterosexual women with a partner, from 18 to 25 years old. In the first phase, we evaluated the propensity for sexual inhibition/excitation and sexual satisfaction of the participants. In the second phase—in the context of a sexuality laboratory—the vaginal pulse amplitude, the rating of sexual arousal, and the rating of genital sensations were evaluated. The participants, distributed in three groups with different levels of sexual satisfaction (p < 0.001), were compared based on the different measures of sexual arousal. The results indicated that the group with lower sexual satisfaction, compared to the group with higher sexual satisfaction, reported more sexual inhibition due to the threat of performance failure (p = 0.011) and due to the threat of performance consequences (p = 0.038). However, no significant differences in sexual arousal status were found between the three groups. In conclusion, the negative association between sexual satisfaction and propensity for sexual inhibition in young women with a partner is supported, but not the positive association between trait/state sexual arousal and sexual satisfaction.